2022
DOI: 10.3389/fnut.2022.938645
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linoleic acid and the ratio of unsaturated to saturated fatty acids are inversely associated with significant liver fibrosis risk: A nationwide survey

Abstract: Since no pharmaceuticals have been proven to effectively reduce liver fibrosis, dietary fatty acids may be beneficial as one of the non-pharmaceutical interventions due to their important roles in liver metabolism. In this cross-sectional study, we analyzed the data from the 2017–2018 cycle of National Health and Nutrition Examination Survey to examine the associations between the proportion and composition of dietary fatty acid intakes with significant liver fibrosis among US population. The dietary fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this sense, Puri et al also reported notably decreased levels of linoleic acid in NASH [ 32 ]. Additionally, it has been shown that the circulating levels of linoleic acid from the diet have an inverse association with the risk of developing hepatic fibrosis [ 33 ]. Linoleic acid levels may be as low as that of an insulin sensitizer, which would imply a maintained persistence of hepatic insulin resistance throughout the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Puri et al also reported notably decreased levels of linoleic acid in NASH [ 32 ]. Additionally, it has been shown that the circulating levels of linoleic acid from the diet have an inverse association with the risk of developing hepatic fibrosis [ 33 ]. Linoleic acid levels may be as low as that of an insulin sensitizer, which would imply a maintained persistence of hepatic insulin resistance throughout the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding linoleic acid metabolism, a study suggested an inverse association between dietary linoleic acid intake and the risk of significant liver fibrosis, particularly emphasizing the ratio of unsaturated to saturated fatty acids[ 19 ]. Another clinical investigation demonstrated that specific alterations in linoleic acid metabolites could differentiate individuals with moderate alcohol-associated hepatitis from those with mild alcohol-associated liver disease among heavy drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Puri et al also reported significantly lower long-chain PUFA concentrations in MASH patients compared to the control group [ 100 ]. In research undertaken by Zhu et al, an analysis of the 2017–2018 National Health and Nutrition Examination Survey data revealed a negative correlation between the ratio of unsaturated to saturated FAs and the likelihood of experiencing significant liver fibrosis in the U.S. population [ 101 ]. Specifically, higher intakes of dietary PUFA and linoleic acid were linked to a decreased risk of significant liver fibrosis.…”
Section: Lipid Synthesis In Masldmentioning
confidence: 99%